The Role of Natural Antioxidants Against Reactive Oxygen Species Produced by Cadmium Toxicity: A Review - Velid Unsal; Tahir Dalkıran; Mustafa Çiçek; Engin Kölükçü (Tabriz University of Medical Sciences, 2020)
Cadmium (Cd) is a significant ecotoxic heavy metal that adversely affects all biological processes of humans, animals and plants. Exposure to acute and chronic Cd damages many organs in humans and animals (e.g. lung, liver, brain, kidney, and testes). In humans, the Cd concentration at birth is zero, but because the biological half-life is long (about 30 years in humans), the concentration increases with age. The industrial developments of the last century have significantly increased the use of this metal. Especially in developing countries, this consumption is higher. Oxidative stress is the imbalance between antioxidants and oxidants. Cd increases reactive oxygen species (ROS) production and causes oxidative stress. Excess cellular levels of ROS cause damage to proteins, nucleic acids, lipids, membranes and organelles. This damage has been associated with various diseases. These include cancer, hypertension, ischemia/perfusion, cardiovascular diseases, chronic obstructive pulmonary disease, diabetes, insulin resistance, acute respiratory distress syndrome, idiopathic pulmonary fibrosis, asthma, skin diseases, chronic kidney disease, eye diseases, neurodegenerative diseases (amyotrophic lateral sclerosis, Parkinson's disease, Alzheimer's disease, and Huntington disease). Natural antioxidants are popular drugs that are used by the majority of people and have few side effects. Natural antioxidants play an important role in reducing free radicals caused by Cd toxicity. Our goal in this review is to establish the relationship between Cd and oxidative stress and to discuss the role of natural antioxidants in reducing Cd toxicity.